Antimicrobial and antipyretic activities of aqueous leaf extract of Spondias mombin Linn. (Anarcadiaceae) - Agbaje, E.O.; Ismail, A.I.; Oguntokun, O.J. (Journal of Medicinal Herbs and Ethnomedicine, 2020)
Spondias mombin (Linn.) (Anacardiaceae) is an herbaceous plant widely used in Traditional African medicine (TAM) for the treatment of diverse ailments including infections and febrile conditions. This study was conducted to investigate the antimicrobial and antipyretic properties of the aqueous leaf extract of S. mombin. The sensitivity test (using zones of inhibition), minimum inhibitory concentration and minimum bactericidal concentration tests were used to investigate its antimicrobial properties, while the 2,4-dinitrophenol (DNP)- and yeast-induced hyperthermia tests were used to investigate antipyretic activity in rodents. S. mombin (50, 100 and 200 mg kg-1, p.o) produced significant (p<0.05) antimicrobial activity in the sensitivity test. The effects of 50, 100 and 200 mg/ml S. mombin were generally comparable to those of ciprofloxacin. Also, S. mombin produced significant (p<0.05) reduction of elevated temperature in the 2,4-DNP and yeast-induced hyperthermia models with peak effects of anti-pyrexia produced at 200 mg kg-1 for 2,4-DNP induced hyperthermia and 100 mg kg-1 for the yeast-induced. The effect at these doses was comparable to that of paracetamol, being the positive control in the two models. The results obtained in this study demonstrated that the aqueous leaf extract of Spondias mombin possesses antibacterial and antipyretic properties.